2020
DOI: 10.2478/cee-2020-0025
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Properties of Plaster Reinforced with Date Palm Fibers

Abstract: This study aims both to investigate the thermal properties of plaster reinforced with date palm fibers and local natural resources valorization to batter using materials construction. For that, studying the effect of addition date palm fibers on the plaster’s thermal properties is a significant point. In this work, we measured effective thermal conductivity, thermal diffusivity, specific heat, and thermal effusivity of date palm fibers reinforced plaster has been studied by CT meter. Samples configurations wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…That is, increasing the DPF contents provides more composite capacity to absorb heat, and this feature enables the composites to be reinforced with fibres in a more insulative way than the control composite. In terms of thermal diffusivity, the results indicated that the addition of palm fibres Rachedi and Kriker [30] researched the thermal properties of plaster reinforced with DPFs. The thermal conductivity of 2% of DPF added to cementitious composite was improved by approximately 50% compared with the control specimens (Figure 41).…”
Section: Thermal Properties Natural Fibre Reinforced Cementitious Com...mentioning
confidence: 99%
See 4 more Smart Citations
“…That is, increasing the DPF contents provides more composite capacity to absorb heat, and this feature enables the composites to be reinforced with fibres in a more insulative way than the control composite. In terms of thermal diffusivity, the results indicated that the addition of palm fibres Rachedi and Kriker [30] researched the thermal properties of plaster reinforced with DPFs. The thermal conductivity of 2% of DPF added to cementitious composite was improved by approximately 50% compared with the control specimens (Figure 41).…”
Section: Thermal Properties Natural Fibre Reinforced Cementitious Com...mentioning
confidence: 99%
“…They also reported in their research that density is mostly related to the thermal conductivity of concrete. Rachedi and Kriker [30] researched the thermal properties of plaster reinforced with DPFs. The thermal conductivity of 2% of DPF added to cementitious composite was improved by approximately 50% compared with the control specimens (Figure 41).…”
Section: Thermal Properties Natural Fibre Reinforced Cementitious Com...mentioning
confidence: 99%
See 3 more Smart Citations